Pendidikan Anak Pada Masyarakat Muslim Transmigran di Desa Huwongo Paguyaman Kabupaten Boalemo Provinsi Gorontalo - Sulfa Potiua (Jurnal Ilmiah Iqra', 2021)
Children's Education in Transmigrant Muslim Communities in Huwongo Paguyaman Village, Boalemo Regency, Gorontalo. This paper aims to find out more about formal and non-formal education in the children of Muslim transmigrants in the village of Huwongo Paguyaman, Boalemo Regency, Gorontalo.In general, various forms of implementation of education have been seen in the Transmigrant community in Huwongo Village. This can be proven by not having a child from this Transmigrant community who has not received an education. This is due to the encouragement and willingness of the parents themselves because for them, whatever the circumstances, children are still obliged to study, especially in formal schools, this is also evidenced by the achievements of the children of the Transmigrant community in Huwongo village very well, this can be seen from the achievements in every the delivery of report cards in each semester at school is always the superior student achievement is the children of the Transmigrant community of Huwongo village compared to the children of the local community, this is due to the encouragement and motivation of their parents - each of the Transmigrants of Huwongo village.As an obstacle to formal education because there is no formal school specifically for the transmigrant community but it does not spark the intention of parents to send their children to school, even junior high and high school are very far from where they live but it is not a barrier to continue their children in school formal.The problem of children's non-formal education in the Muslim community of Transmigrants in Huwongo Village is not directly proportional to the progress of their formal education. This evidenced by the author's observations and the results of interviews with the community as well as the acknowledgment of the management that there are many obstacles regarding this non-formal education, which is caused by the lack of encouragement from the community. parents and also lack of awareness of the children themselves